A Decomposition-Based Approach to Byzantine-Resilient Distributed State Estimation - Gao, Rui; Chai, Tianyou (Chinese Control and Decision Conference, 2025)
This paper is concerned with the problem of resilient distributed state estimation for a linear system using a network of agents, some of which are subject to the Byzantine attacks. By introducing a refined canonical decomposition form of the system, a novel resilient distributed state estimation strategy is proposed. Necessary and sufficient conditions under which the regular agents can still asymptotically estimate the state of the system despite the adversarial behaviors of the Byzantine agents are established. In contrast to the existing Jordan canonical form-based strategies, the proposed strategy can reduce the measurement redundancy requirement of the agents in the network. Finally, an example is given to demonstrate the effectiveness of the proposed strategy.